The impact of human papillomavirus genotype on colposcopic appearance: a cross‐sectional analysis. (4th February 2014) - van der Marel, J; van Baars, R; Quint, WGV; Berkhof, J; del Pino, M; Torné, A; Ordi, J; Wentzensen, N; Schiffman, M; van de Sandt, MM; Lindeman, J; Jenkins, D; et al.
<x xml:space="preserve">Abstract</x> Objective To study colposcopic performance in diagnosing high‐grade cervical intraepithelial neoplasia or cervical cancer (CIN2+ and CIN3+) using colposcopic characteristics and high‐risk human papillomavirus (hrHPV) genotyping. Design Cross‐sectional multicentre study. Setting Two colposcopy clinics in The Netherlands and Spain. Population Six hundred and ten women aged 17 years and older referred for colposcopy because of abnormal cytology. Methods A cervical smear was obtained. Colposcopists identified the worst lesion, graded their impression and scored the colposcopic characteristics of the lesions. Up to four biopsies were collected, including one biopsy from visually normal tissue. Main outcome measures CIN2+ and CIN3+, positive for HPV16 or other high‐risk HPV types (non‐16 hrHPV‐positive). Results The mean age in HPV16‐positive CIN2+ women was 35.1 years compared with 39.1 years in women with other hrHPV types (P = 0.002). Sensitivity for colposcopy to detect CIN2+ was 87.9% (95%CI 83.2–91.5), using colposcopic cut‐off of 'any abnormality'. The remaining CIN2+ were found by a biopsy from visually normal tissue or endocervical curettage (ECC). Detection of CIN2+ by lesion‐targeted biopsies was not different between HPV16‐positive women [119/135; 88.1% (95%CI 81.2–92.9)] and non‐16 hrHPV‐positive women [100/115; 87.0% (95%CI 79.1–92.3); P = 0.776]. In multivariate analysis, 'acetowhitening' [odds ratio (OR) 1.91, 95%CI 1.56–3.17], 'time of appearance' (OR 1.95, 95%CI 1.21–3.15) and 'lesion >25% of visible cervix' (OR 2.25, 95%CI 1.44–3.51) were associated with CIN2+. Conclusions In this population following European screening practice, HPV16‐related CIN2+ lesions were detected at younger age and showed similar colposcopic impression as non‐16 hrHPV high‐grade lesions. There was no relationship between any of the colposcopic characteristics and HPV16 status.